A situation of multilateral co-operation: the "couple hote-vecteur performant" program (CHVP). (11th May 2004) - Estades, Jacqueline
This paper presents a situation of multilateral co-operation, focusing its analysis primarily on co-ordination between actors. Two forms of regulation interact in the national program studied: local regulation comprising a hierarchy and trust, and global regulation characterising a French model of innovation. While this mode of organising research-industry co-operation favours the development of pre-competitive research, its ability to produce inter-firm cooperation on strategic research is more hypothetical.